Microsoft Dynamics 365 Project Operations - Houdeshell, Robert (Packt Publishing, 2021)
Discover the endless capabilities and end-to-end project management functionalities of Dynamics 365 Project Operations to drive your firm's project success and ensure rapid business growth in the competitive digital economic world Key Features Deliver successful projects via improved collaboration, visibility, and teamwork using Microsoft Project Operations solutions Gain real-time data insights to modernize business strategies to increase market share Build the right project operations models to meet business needs with an optimized budget Book Description Dynamics 365 Project Operations is a game-changing solution set for project-driven businesses that allows you to deliver commercially successful projects in a timely and cost-effective manner, keeping the project teams productive and collaborative. With this book, you'll find out how you can bring more value to the business by winning new projects and driving exponential revenue growth. Starting with the key principles of Project Operations, you'll understand how it improves project planning and execution. You'll then learn how to successfully deploy Project Operations along with different integration strategies and get to grips with the best approach for sales through project opportunities, project contracts, and pricing workflow implementation. This book will guide you through setting up direct staffing and centralized staffing models and enable you to manage project changes confidently by getting hands-on with project timeline management, pricing management, resource assignments, and modifications. In the final chapters, you'll find out how to use Project Operations effectively for project accounting and finance. By the end of this book, you'll have gained the confidence to deliver profitable projects in a well-connected organization through efficient decision-making and successful customer-client relationships. What you will learn Configure key elements of Project Operations to drive improved collaboration with your customers Discover how Project Operations is interconnected with Microsoft 365 and Dynamics 365 Platform Understand the Project Opportunity-to-Quote-to-Contract workflow and its implications for selling Find out how to set up and utilize direct staffing and centralized staffing models Explore Project Timeline Management using Task, Board, and Timeline views Find out how information flows to finance and operations in Project Operations Who this book is for This book is for pr ...